1970
DOI: 10.1017/s0022172400042455
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the serological response to Yersinia enterocolitica and Brucella abortus in cattle

Abstract: SUMMARYThe serological responses of cattle to inoculation with Brucella abortus and Yersinia enterocolitica type IX were compared. Complete cross-reactions were found in serum agglutination, antiglobulin, complement fixation and Rose Bengal plate tests. The cross-reaction between Br. abortus and Y. enterocolitica IX was confirmed by immunodiffusion tests. Although antibodies specific for each organism could also be detected by immunodiffusion tests with high titre rabbit or bovine sera, these tests were insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Cross-reactivity between Vibrio cholerae and Brucella species is widely known (Eisele, McCullough, Beal & Burrows, 1946;Gallut, 1950;Mathur, 1960) and has recently been again emphasized by Feeley (1969) and Gangarosa, DeWitt, Feeley & Adams (1970), who found other instances of the presence of vibriocidal antibody in human sera in the absence of exposure to cholera infection. Corbel & Cullen (1970) Immune sera against V. cholerae Ogawa and Inaba were prepared in rabbits (four for each serotype) by injecting live saline suspensions from a 7 hr.-old growth (at 370 C.) on heart infusion agar containing about 2 x 109 organisms per ml. Each of the rabbits received three intravenous injections, 5 days apart, of 0-25, 0.5, and 0-5 ml.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-reactivity between Vibrio cholerae and Brucella species is widely known (Eisele, McCullough, Beal & Burrows, 1946;Gallut, 1950;Mathur, 1960) and has recently been again emphasized by Feeley (1969) and Gangarosa, DeWitt, Feeley & Adams (1970), who found other instances of the presence of vibriocidal antibody in human sera in the absence of exposure to cholera infection. Corbel & Cullen (1970) Immune sera against V. cholerae Ogawa and Inaba were prepared in rabbits (four for each serotype) by injecting live saline suspensions from a 7 hr.-old growth (at 370 C.) on heart infusion agar containing about 2 x 109 organisms per ml. Each of the rabbits received three intravenous injections, 5 days apart, of 0-25, 0.5, and 0-5 ml.…”
Section: Introductionmentioning
confidence: 99%
“…Cpm = mean counts per minute of triplicate cultures (control), without specific antigen or mitogen. (15,29), the organism appears to be non-pathogenic for bovines (6). As of now, there is no evidence that Br.…”
Section: Results Of Brucellin Skin Testmentioning
confidence: 95%
“…Because of these common antigenic determinants, it is apparent that any serological test employing Brucella antigen containing Brucella lipopolysaccharide would be unsuitable for differentiating brucellosis from yersiniosis. Realising the full implications these cross-reactions would have the serological diagnosis of bovine brucellosis, many investigators (6,26,27) have attempted to develop methods of differentiating the two infections. A review of these differentiating assays by Mittal and Tizard (28) indicated clearly that none of them is fully satisfactory.…”
Section: Results Of Brucellin Skin Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Yersinia enterocolitica ZX shows complete cross-agglutination with Brucella and tests with monospecific antiserum have shown that the cross-reacting antigen of Y. enterocolitica ZX contains determinants of similar specificity to the A determinants of B. abortus (Corbel & Cullen, 1970). Yersinia enterocolitica NCTC 10461 does not cross-react serologically with Brucella.…”
Section: Discussionmentioning
confidence: 99%